The Effect of Planting Media and Taerh Bean Sprout POC on the Growth of Red Betel Setek - Siti Aisyah; Dini Anggorowati; Siti Hadijah (Fakultas Pertanian Universitas Tanjungpura, 2019)
This study aims to determine the interaction of planting media and the concentration of POC bean sprouts that provide the best growth of red betel cuttings. This research was carried out from February to May 2018 in the Maya Island sub-district of Kemboja village. The study used factorial experimental methods with a completely randomized design (CRD) consisting of two factors, namely planting media (m) POC bean sprouts (p). The media consists of two levels, namely (husk charcoal and manure soil), POC factor consists of 4 levels, namely (0%, 20%, 40%, and 60%), there are 8 combinations of treatments with 3 replications and each replication consists of 3 sample plants. The combination of treatments meant is m1p0, m1p1, m1p2, m1p3, m2p0, m2p1, m2p2, and m2p3. Observation variables observed were cut length (cm), number of leaves (strands), root volume (cm3), and shoot dry weight (g). The results showed that there was a significant interaction in root volume and dry weight, and gave the highest mean treatment (soil and manure + POC 40%), which was 2.63 cm3 for root volume and 1.56 g for shoot dry weight.Keyword : land, husk charcoal, manure, POC bean sprouts